Employment Outcomes and Job Quality of Vocational Rehabilitation Consumers With Deaf-Blindness. (October 2019) - McDonnall, Michele C.; Cmar, Jennifer
The purpose of this study was to investigate employment outcomes for vocational rehabilitation (VR) consumers with deaf-blindness, a population that has received no attention in the literature. The sample was obtained from Rehabilitation Services Administration Case Service Report (RSA-911) data and included 1, 382 consumers with deaf-blindness identified as their primary or secondary disability whose cases were closed during fiscal years 2013, 2014, and 2015. Independent variables consisted of consumer personal characteristics and VR service-related variables. Two measures of employment outcomes were used: obtainment of competitive employment and a composite measure of job quality. Overall, the results indicate that several VR service-related factors are associated with whether deaf-blind consumers obtain competitive employment, but consumers' personal characteristics are much more important in determining job quality. Implications for improving employment outcomes for consumers who are deaf-blind include providing job-related services, supporting educational advancement, and providing counseling and guidance. Results also support the importance of accounting for employment status at application in RSA-911 analyses and the efficacy of service provision by separate agencies for the blind.